Preferensi Minat Masyarakat Kota Palangka Raya Bertransaksi Menggunakan Kartu Pembayaran Elektronik Berlogo Gerbang Pembayaran Nasional Bank Indonesia - Muhamad Reza Humaidi; Sofyan Hakim (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2019)
The purpose of this research is to are effort from office unit Indonesia Bank Province Kalimantan Tengah to attract people’s interest in Palangka Raya on transaction using Electric Payment Card named National Payment Gateway from Indonesia Bank and the Preference peoples’ interest in palangka Raya on Transaction using Electric Payment Card named National Payment Gateway from Indonesia Bank. This research used qualtitative descriptive method, the subject of this research were Unit Manager Payment Surveillance System , Rupiah Management, Inclusive Finance (UPPSPPURKI) of Office Unit Indonesia Bank Province Kalimantan Tengah, Manager Unit Operational Payment System ( UOSP) of Indonesia Bank Province Kalimantan Tengah which used using Electric Payment Card named National Payment Gateway from Indonesia Bank.The result of this research shows that : (1) The efforts from office unit Indonesia Bank Province Kalimantan Tengah to attract people’s interest in Palangka Raya on transaction using Electric Payment Card named National Payment Gateway from Indonesia Bank can be see like in  last year or 2018 they published to the people through social media, electronic media and printed media and also launching, campaign, socialiszation, Week trade NPG card .  While in 2019, they plan two big events related with National Payment Gateway or socialiszation the NPG to the people like students and that events not to different with the last year events. (2) The main Preference to attract people’s interest in Palangka Raya on transaction using Electric Payment Card named National Payment Gateway from Indonesia Bank was from the internal, 15 from 19 respondents said that the main factors were comfortable, Simpleness transaction with the features and standardize services, and the cheaper cost that the card before it like Visa or Mastercard.